(untitled) (Conferencea, 2022)
In order to raise the degree of student interest in the educational process and learning in general, the article illustrates a difficulty with developing motivation to learning activities among impaired students at higher education institutions. The importance of higher education institutions in ensuring a young person’s assimilation into society is emphasized. A vocational education will make sure that a student achieves both financial and personal independence. An overview of recent studies on what drives impaired individuals to pursue higher education is provided. The variables influencing students with health restrictions’ motivation to pursue higher education are listed. Such students’ (cognitive, social, and practical) learning and professional motives are explained in depth. Their professional choices and personal, social, organizational, and interpersonal demotivators are listed as learning deterrents. It is concluded that while the professional and learning goals of disabled students and regular students are similar overall, the unique living circumstances of disabled students are the factors impeding the development of educational programs and necessitating additional measures to support disabled students’ learning activity. The essay provides incentives to boost impaired pupils’ motivation.